ANALYSIS OF EX-COMMERCIAL FOSTERING SEX WORKERS GUIDANCE PROGRAM AT THE INTEGRATED SERVICE UNIT OF SOSIAL REHABILITATION FOR SOCIAL DISABILITY - Risnaeni; Idris; Mahardiana, Lina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
The purpose of this study was to determine the growth in number of former commercial sex workers in the Integrated Service Unit of the Social Rehabilitation Center for Persons with Social Disabilities of Central Sulawesi Province. Descriptive qualitative research was used in this study. Observation, interviews, documents, and reference search were used to collect data. Primary and secondary data sources were used. Three steps consisted of data reduction, data presentation, and conclusion drawing in the data processing and analysis procedure. The research findings show that The Integrated Service Unit of Social Rehabilitation for Social Disability Central Sulawesi Province uses various strategies to build human resources for former commercial sex workers. There are five types of guidance: 1) mental health guidance, 2) physical guidance, 3) social guidance, 4) skills guidance, and 5) spiritual guidance. Related to the development of human resources for former commercial sex workers, there are obstacles or barriers that arise in the process that must be overcome so that a company can be successful. In addition to the delay in receiving funds from The Integrated Service Unit of Social Rehabilitation for Social Disability of Central Sulawesi Province, the obstacles to the activities carried out by these organizations include many of their clients who return to being prostitutes after previously no longer working. received a positive response from them. Former commercial sex workers at The Integrated Service Unit of Social Rehabilitation for Social Disability Central Sulawesi Province are part of a human resource development model consisting of three parts: 1) rehabilitation (physical, social, and mental development); 2) resocialization (entrepreneurship and health socialization); and 3) additional guidance (social and skills development).